need guidance on an algebra problem

posted by .

20 x+3(y-1)=11
2(x-y)+8y = 28

multiply out
20 x+3y-3=11 - Is this correct?

2x+14y = 28

Using the addition method, would you multiply the first problem by 2 and the second by 20?

No. In the second multiply out, you should have gotten

2x -1y+8y=28 or

No, in the addition method
multiply the second equation by ten, then subtract one from the other.

Bob, I read the questions as
x+3(y-1)=11 ------> x+3y = 14 and
2(x-y)+8y = 28----> 2x-2y+8y=28 or x+3y=14

which are two identical equations.
I think the 20 was the question number.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math help please

    I am having a hard time understanding recprocial with fractions I would like to find a web site to help me understand this better I have a problem that is need to know if i have done it right the question is find the reciprocial of …
  2. math,correction

    Can someone correct these for me please.. Find the value of the polynomial 8x – 6 when x = 1 and when x = –1. My answer: So when x = 1 the value of the polynomial is: 2And when x = -1 the value of the polynomial is: -14 Multiply. …
  3. Math

    i need help finding the slope of the line that passes through each pair of poinst. 1. (1,-3),(4,3) 2.(5,0), (-2,1) Divide (y2 - y1) by (x2 - x1). For (1), this would be 6/3 = ?
  4. algebra

    if you have the sign of > or < does this also mean = ?
  5. Math

    8*2sq+7*(4+1)= ? Can someone explain to me what to after the parenthesis?
  6. Algebra

    How do I solve for elimination method on this problem: 0.3x - 0.2y=4 and 0.3x + 0.3y= 5/19. I know that multiply by 10 on both equations and get 3x-2y=40 and 3x+3y=50/19. and then I have to multiply 3x-3y=40 by 3 and 3x+3y= 50/19 by …
  7. Math

    The problem to solve is: (x+20)(x-12)(x+4)>0 but I can't figure out how to do this right so I left off the >0 and tried to solve the equation. x+20 evaluates to x+20 x-12 evaluates to x-12 Multiplying x+20 by x-12 is a classic …
  8. Math Uugghhh

    Okay the problem says I have to multiply (-2t)^2(3t^7)^2 SO what am I supposed to do, add the exponents then multiply -2t by 3t?
  9. algebra II

    Select the best possible first step to solving the system by first eliminating the y variable. x + 8y = –4 2x – 4y = –13 Multiply the first equation by 2. Multiply the second equation by 2. Multiply the first equation by –2. …
  10. math

    ms.sue help asap 1. which exponent makes the statement true?

More Similar Questions